Molecular weight driving bioavailability and intrinsic degradation mechanisms of dissolved organic phosphorus in lake sediment. (15th February 2022) - Ni, Zhaokui; Huang, Dongling; Xiao, Mengqi; Liu, Xiaofei; Wang, Shengrui
Highlights: Major DOP contributor in lake sediments is LMW (63.8%) Bioavailable DOP species were decreased with decreasing MW Microbial utilization and DOM characteristics determine DOP hydrolysis in different MWs Large accumulation of LMW-DOP has a high vulnerability to degradation in natural environment Abstract: The sediment dissolved organic phosphorus (DOP) for the "internal phosphorus (P) loading" has raised intensive concern, but its bioavailability and intrinsic degradation mechanism have not been fully elucidated. In this work, multi-techniques were combined to construct the response of sediments DOP's bioavailability to molecular weight (MW) based on ten lakes of China, thereby elucidating the intrinsic degradation mechanism of sediment DOP. A high percentage (74.5% on average) and significantly positive correlations with respect to different MWs were observed, highlighting the importance of DOP to dissolved P in sediments. DOP is mainly composed of a low MW (LMW) portion (63.8%) and the substances are primarily derived from microbial sources. Bioavailable DOP species were closely related to MW, with labile monoester P and diester P decreased with decreasing MW. Analysis of environmental processes showed that microbial utilization capacity and the characteristics of dissolved organic matter (DOM) with different MWs were the dominant drivers in determining the bioavailability of DOP. That is, microorganisms exhibit high DOM utilization capacity in LMW portion, promoting the degradation and transformation of bioavailable DOP species. Furthermore, the increased humic and fulvic-like substances by microbial degradation might in turn inhibit the enzymatic hydrolysis of LMW-DOP. This pattern explains why the contents of LMW-DOP are very high, but it contains less bioavailable DOP. By studying the bioavailability of sediment DOPs with different MWs, it is found that, under natural conditions, labile monoester and diester P in LMW-DOP have a high tendency to degrade than those in HMW-DOP. The results further show that, microbial utilization and DOM characteristics, as well as their linkage with DOP's bioavailability and degradability, have important implications for assessing DOP's degradation potential. The insights from this study might shed light on more effective strategies for mitigating the risks of "internal P loading". Graphical abstract: Image, graphical abstract